2013
DOI: 10.5755/j01.ms.19.4.2670
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Synthesis, Structural and Optical Properties of Cerium-Doped Strontium Aluminates, Sr3Al2O6 and SrAl12O19

Abstract: In this study, an aqueous sol-gel synthesis method was applied for the preparation of strontium aluminate (Sr 3 Al 2 O 6 and SrAl 12 O 19 ) ceramics. The structural properties of these compounds were investigated by X-ray powder diffraction analysis. The obtained data were analysed employing Rietveld method. Optical properties of sol-gel derived ceriumdoped strontium aluminates showed emission maxima at 480 nm and 317 nm for Sr 3 Al 2 O 6 :Ce and SrAl 12 O 19 :Ce, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The peaks in the wavelengths of 410 nm are attributed to Ce 3+ 5d-4f transitions in SHO according to the previous reports [11][12][13]. Ce 3+ 5d-4f emission of Ce doped SAO at 310 nm reported by other groups [16,17] was not detected. Fig.…”
Section: Crystal Growthmentioning
confidence: 34%
“…The peaks in the wavelengths of 410 nm are attributed to Ce 3+ 5d-4f transitions in SHO according to the previous reports [11][12][13]. Ce 3+ 5d-4f emission of Ce doped SAO at 310 nm reported by other groups [16,17] was not detected. Fig.…”
Section: Crystal Growthmentioning
confidence: 34%
“…Journal Pre-proof which their doping with cerium has also been reported [26,27]. Owing to the complexity of the elongated phase observed in Fig.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 61%
“…The atmospheric oxygen during annealing in air at high temperatures may get diffused in the matrix altering the composition or forming small clusters of new phase(s). 83,84 The phase transition from monoclinic a-phase to hexagonal b-phase on heating in the range of 650-700 °C and also under a load to twinning pseudo-elastic deformation may enhance the accumulation of surface charges. On the basis of these results, Matsuo et al 81 have suggested the ML mechanism in SAOE that twinning pseudo-elastic deformation under a load creates a local electric eld around the twin interface.…”
Section: Optimization Of Impurity Concentration By ML Studies By Comp...mentioning
confidence: 99%
“…Holes then excite Eu 1+ to produce Eu 2+* , which then returns to the ground state by emitting a green light at around 520 nm. 83,84 The traps may be regenerated by irradiation with UV-radiation. 85,86 However, it does not explain the self-reproducible ML aer annealing the material between 80 and 300 °C.…”
Section: Optimization Of Impurity Concentration By ML Studies By Comp...mentioning
confidence: 99%